Unıversal legal standards of sustaınable socıalıty from the context of the rıght to a decent lıfe - M. S. Rahımova (Науковий вісник Ужгородського національного університету. Серія Право)
In the modern era, sustainable development is about meeting the needs of the present generation without compromising the interests of future generations, which is characterized by its three reference points. Sustainable sociality, which is one of the strongest pillars, occupies one of the most important places in ensuring a decent standard of living for people. Society can achieve the improvement of people’s well-being by adequately ensuring their basic rights within the framework of sustainable sociality. In other words, Sustainable development is the activity of using all means to protect humanity in the most ideal form and to preserve its existence for a long time. This activity treats everyone equally without distinction between generations and is aimed at dividing natural resources equally among them, and ultimately implies the activities of governments aimed at uninterrupted but fully satisfied needs. States should implement policies aimed at protecting the rights of not only their current but also potential citizens in the future and should protect the rights of everyone equally without applying any distinctions in time.